2015
DOI: 10.3390/ma8115434
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cotton-Wool-Like Poly(lactic acid)-Based Composites Consisting of Core-Shell-Type Fibers

Abstract: In previous works, we reported the fabrication of cotton-wool-like composites consisting of siloxane-doped vaterite and poly(l-lactic acid) (SiVPCs). Various irregularly shaped bone voids can be filled with the composite, which effectively supplies calcium and silicate ions, enhancing the bone formation by stimulating the cells. The composites, however, were brittle and showed an initial burst release of ions. In the present work, to improve the mechanical flexibility and ion release, the composite fiber was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In vivo, newly formed bone was observed in 4 weeks, and the defect was covered in 12 weeks. Kasuga et al reported cotton-like SiV/PLLA composites prepared by an electrospinning method, and the composites showed excellent bioactivity and ease of handling for bone-filling surgery [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, newly formed bone was observed in 4 weeks, and the defect was covered in 12 weeks. Kasuga et al reported cotton-like SiV/PLLA composites prepared by an electrospinning method, and the composites showed excellent bioactivity and ease of handling for bone-filling surgery [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…SEM images of fractured (3:3) coaxial fibres (figure 3(a)) did not show an exposed core layer as some studies suggest [17][18][19], however, it did show a few hollow fibres. TEM cross-sectional images show clearly the core and shell configuration and the surface porosity, but no mixing between the layers.…”
Section: Discussionmentioning
confidence: 89%
“…A coaxial electrospinning setup was used to create a polymeric core-shell non-woven fabric within which the inorganic particles were loaded in the core of the bres protected by a polymeric shell. 20 One important criterion of this engineered system is that the shell layer must uptake water from the surrounding body uid in order to trigger the hydrolytic degradation of the inorganic particles and subsequent diffusion of the therapeutic ions in the media.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Poly(D,L-lactide-co-glycolide) (PLGA) was selected has an outer layer for its ability to uptake water and therefore allowing the hydrolytic degradation of the enclosed SiV particles. 20,29,30 The effect of the relative diameter of the inner core to the size of the PLGA shell on the mechanical properties, dissolution behaviour, and apatite nucleation was investigated.…”
Section: Introductionmentioning
confidence: 99%